(untitled) (Sirte University Journal of Humanities, 2023)
The aim of this study is to investigate the experiences of the national reconciliation in post-conflict era in three African countries: South Africa, Rwanda, and Algeria. This study discusses the lessons learned from these experiences that may be applied on the Libyan case. Thus, the research question of the study is formed as follows: To what extent the three African countries were able to succeed in the process of national reconciliation? The study concluded that despite the differences between the three experiences, all of the three countries agreed on the fact that the will and the support of the political system were very crucial in the process of national reconciliation. The three countries worked to establish institutions for national reconciliation, activate the judiciary, apply transitional justice, start public trials, redress grievances, and pardon the penitents. This confirms the importance of a political will for achieving national reconciliation, which must be exist in the Libyan case.